Machinability investigation and sustainability analysis of minimum quantity lubrication–assisted micro-milling process. (September 2020) - Yang, Xueming; Cheng, Xiang; Li, Yang; Zheng, Guangming; Xu, Rufeng
Machining conditions such as cutting fluids exert a crucial function in micro-milling, which removes chips from the cutting area and lubricates the interface between the tool and workpiece. Therefore, it is necessary to identify suitable cutting fluids for processing different materials. In this article, the effects of cutting fluids (dry, flood cooling, minimum quantity lubrication, and jet cold air) on tool wear, surface roughness, and cutting force were studied. The Pugh matrix environmental approach was used to compare different cutting fluids in terms of sustainable production. In addition, a curved thin wall was processed to demonstrate the value of minimum quantity lubrication in industry. The experimental results illustrated that the minimum quantity lubrication can not only effectively reduce tool wear and cutting force but also improve the finished surface quality. According to the sustainability assessment results, minimum quantity lubrication was superior to other cutting fluids in terms of environmental impact and production quality. The curved thin wall size error was only 2.25% under minimum quantity lubrication condition. This indicated minimum quantity lubrication was particularly suitable for micro-milling of H59 brass and 6061 aluminum compared to other cutting fluids.